Neonatal thrombosis. (19th March 2022) - Makatsariya, Alexander; Bitsadze, Viktoriya; Khizroeva, Jamilya; Vorobev, Alexander; Makatsariya, Natalya; Egorova, Elena; Mischenko, Alexander; Mashkova, Tamara; Antonova, Alexandra
Abstract: Neonatal thromboembolism in pediatric patients is a rare but life-threatening condition mainly caused by combinations of at least 2 prothrombotic triggering risk factors such as the central venous lines, septic condition, and prematurity. Other risk factors include asphyxia, dehydration, liver dysfunction, inflammation, and maternal condition. Neonatal hemostatic system is different from one of the older children and adults. Coagulation proteins do not cross the placenta but are synthesized in the fetus from an early stage. In the term neonate, concentrations of several procoagulant proteins, particularly the vitamin K dependent and contact factors are reduced when compared with adults. Conversely, levels of antithrombin, heparin cofactor II and protein C and S are low at birth and fibrinolysis system is characterized by the decreased level of plasminogen and alpha-1-antiplasmin, increased tissue plasminogen activator. These features all tend to be gestational dependent and are more present in the preterm infant. Primarily in this context neonates appear to be at a higher risk of thrombosis than older children. Thrombotic complications reach their peak in the group of children born at 22–27 weeks. The role of inherited thrombophilic risk factors in neonatal VTE development is poorly defined. The presence of inherited and acquired thrombophilia in mother and newborn is also responsible for the development of thrombosis in neonates and should be considered. Thrombophilia in the mother can lead to increased coagulation potential and prethrombotic conditions during pregnancy, causing thrombotic vasculopathy at the placental level. The benefit of identifying thrombophilia in the sick preterm newborns who are in the group of risk for development of thrombotic complications may facilitate the thromboprophylaxis. Further research regarding assessment of risk factors, diagnostics and treatment strategy is required.